(untitled) (American Journal of Islam and Society, 1998)
Early Saturday morning on 16 May 1998, fifty people made their way into the conference room of Georgetown University’s Salaam Intercultural Center for the first annual conference of the Association of Contemporary Muslim Philosophers. Looking into their eyes, one could see a glimmer of hope and the fire of enthusiasm. Clearly, this was not going to be a run of the mill encounter of Muslim minds. Some of the greatest intellects of the Muslim world were present, among them Professor Seyyed Hossein Nasr, Dr. Taha B Jabir al ‘Alwani, and Dr. Kamal Hassan. Young students with fresh countenances and effervescent comments waited to deliberate upon such issues as the difference between public and private philosophy, the role of postmodernism in the Muslim world, and why and in what condition does the Muslim intellectual tradition find itself. Ironically, this occurred in view of an immense Jesuit Crucifix heralded by the Greek letters alpha and omega, which symbolize Christ. While for some this signified the contradiction and turmoil present within current Muslim philosophical discourse, for others it embodied a promising message. For those who saw it as a positive symbol, including myself, the cross served to illustrate the universe, marking the four cardinal directions of space, and the surrounding alpha and omega symbolized the all-encompassing nature of the Qur’an. On a terrestrial level, it verified the resilient nature of the Muslim intellect for, quite obviously, we were a group of Muslims meeting in a Jesuit institution to talk about reviving Islamic philosophy. Nevertheless, the universal significance of that symbol was realized by the spirit of the gathering and in the profound discussions afforded by all those present. The conference started with a moment of reflection upon the verses of the Qur’an found in Surat al ‘Alaq: ...